Habituation of the cardiovascular response to restraint stress is inhibited by exposure to other stressor stimuli and exercise training - Benini, Ricardo [UNESP]; Oliveira, Leandro A. [UNESP]; Gomes-De-Souza, Lucas [UNESP]; Rodrigues, Bruno; Crestani, Carlos C. [UNESP] (The Company of Biologists, 2020)
This study evaluated the effect of exposure to either a chronic variable stress (CVS) protocol or social isolation, as well as treadmill exercise training, in the habituation of the cardiovascular response upon repeated exposure to restraint stress in rats. The habituation of the corticosterone response to repeated restraint stress was also evaluated. For this, animals were subjected to either acute or 10 daily sessions of 60 min of restraint stress. CVS and social isolation protocols lasted for 10 consecutive days, whereas treadmill training was performed for 1 h per day, 5 days per week for 8 weeks. We observed that the increase in serum corticosterone was reduced during both the stress and the recovery period of the 10th session of restraint. Habituation of the cardiovascular response was identified in terms of a faster return of heart rate to baseline values during the recovery period of the 10th session of restraint. The increase in blood pressure and the decrease in tail skin temperature were similar at the 1st and 10th session of restraint. Exposure to CVS, social isolation or treadmill exercise training inhibited the habituation of the restraint-evoked tachycardia. Additionally, CVS increased the blood pressure response at the 10th session of restraint, whereas social isolation enhanced both the tachycardia during the first session and the drop in skin temperature at the 10th session of restraint. Taken together, these findings provide new evidence that pathologies evoked by stress might be related to impairment in the habituation process to homotypic stressors.
Keywords: Adaptation; Blood pressure; Chronic variable stress; Corticosterone; Heart rate; Social isolation